DNA damage in human whole blood caused by radiopharmaceuticals evaluated by the comet assay - Schmeiser, Heinz; Mier, Walter; Kiß, Oliver; Dimitrakopoulou-Strauss, Antonia; Schmezer, Peter; Kratochwil, Clemens; Kopka, Klaus (Mutagenesis, 2019)
Radiopharmaceuticals used for diagnosis or therapy induce DNA strand breaks, which may be detectable by single-cell gel electrophoresis (called comet assay). Blood was taken from patients before and at different time points after treatment with radiopharmaceuticals; blood cells were investigated by the comet assay using the percentage of DNA in the tail as the critical parameter. Whereas [225Ac]Ac-prostate-specific membrane antigen (PSMA)-617 alpha therapy showed no difference relative to the blood sample taken before treatment, beta therapy with [177Lu]Lu-PSMA-617 3 h post-injection revealed a small but significant increase in DNA strand breaks. In blood of patients who underwent positron emission tomography (PET) with either [18F]2-fluor-2-deoxy-D-glucose (FDG) or [68Ga]Ga-PSMA-11, an increase of DNA migration determined by the comet assay was not found when analysed at different time points (2–70 min) after intravenous tracer injection. Human whole blood was incubated with the targeted clinically relevant therapeutic radiopharmaceuticals [225Ac]Ac-PSMA-617, [177Lu]Lu-PSMA-617 and [90Y]Y-DOTA(0)-Phe(1)-Tyr(3)-octreotide (DOTA-TOC) at different activity concentrations (kBq/ml) for 5 days and then analysed by the comet assay. DNA damage increased with higher concentrations of all radiolabeled compounds tested. [177Lu]Lu-PSMA-617 caused higher blood cell radiotoxicity than equal activity concentrations of [90Y]Y-DOTA-TOC. Likewise, whole human blood was exposed to the positron emitters [18F]FDG and [68Ga]Ga-PSMA-11 in vitro for 24 h with activity concentrations ranging between 5 and 40 MBq/ml. The same activity concentration dependent elevated DNA migration was observed for both compounds although decay energies are different. This study demonstrated that the amount of DNA damage detected by the comet assay in whole human blood is similar among different positron emitters and divergent by a factor of 200 between alpha particles and beta radiation.
Gesehen am 04.11.2019